The Oxford handbook of law, regulation and technology - Brownsword, Roger; Scotford, Eloise, 1978-; Yeung, Karen (Oxford : Oxford University Press, 2016)
Bringing together leading scholars from law and other disciplines to explore the relationship between law, technological innovation, and regulatory governance, this handbook is organised into five parts. After providing an overview and identifying major themes, the sections focus on specific challenges and provide critical exploration of the issues.
Law, Regulation and Technology: the Field, Frame and Focal Questions / Roger Brownsword, Eloise Scotford, Karen Yeung -- Conflict of Laws and the Internet / Uta Kohl -- Technology and the American Constitution / Stephanie A. Maloney, O. Carter Snead -- Contract Law and the Challenges of Computer Technology / Stephen Waddams -- Criminal Law and the Evolving Technological Understanding of Behaviour / Lisa Claydon -- Imagining Technology and Environmental Law / Elizabeth Fisher -- Parental Responsibility; Hyper-parenting and the Role of Technology / Jonathan Herring -- Law, Liberty, and Technology / Roger Brownsword -- Public International Law and the Regulation of Emerging Technologies / Rosemary Rayfuse -- Torts and Technology / Jonathan Morgan -- The Legal Institutionalization of Public Participation in the EU Governance of Technology / Maria Lee -- The Role of Non-state Actors and Institutions in the Governance of New and Emerging Digital Technologies / Mark Leiser, Andrew Murray -- Equality: Old Debates, New Technologies / Jeanne Snelling, John McMillan -- Surveillance Theory and its Implications for Law / Tjerk Timan, Maša Galič, Bert-Jaap Koops -- Automatic Justice? Technology, Crime and Social Control / Amber Marks, Ben Bowling, Colman Keenan -- Debating Autonomous Weapon Systems, their Ethics and their Regulation under International Law / Kenneth Anderson, Matthew C. Waxman -- Hacking Metaphors in the Anticipatory Governance of Emerging Technology: The Case of Regulating Robots / Meg Leta Jones, Jason Millar -- Challenges from the Future of Human Enhancement / Nicholas Agar -- Novel Foods and Risk Assessment in Europe: Separating Science from Society / Robert Lee -- From Improvement towards Enhancement: A Regenesis of EU Environmental Law at the Dawn of the Anthropocene / Han Somsen -- Human Rights and Human Tissue: the Case of Sperm as Property / Morag Goodwin -- Legal Evolution in Response to Technological Change / Gregory N. Mandel -- Regulating Workplace Technology / Tonia Novitz -- Law and Technology in Civil Judicial Procedures / Francesco Contini, Antonio Cordella -- Tax Law and Technology Change / Arthur J. Cockfield -- Regulating in the Face of Sociotechnical Change / Lyria Bennett Moses -- Liberal Democratic Regulation and Technological Advance / Tom Sorell, John Guelke -- Precaution in the Governance of Technology / Andy Stirling -- Hardwiring Privacy / Lee A. Bygrave -- Race and the Law in the Genomic Age / Robin Bradley Kar, John Lindo -- Data-Mining as Global Governance / Fleur Johns -- New Technologies, Old Attitudes and Legislative Rigidity / John Harris, David R. Lawrence -- Transcending the Myth of Law's Stifling Technological Innovation / t Population, Reproduction and Family / Sheila A.M. McLean -- Reproductive Technologies and the Search for Regulatory Legitimacy / Colin Gavaghan -- Technology and the Law of International Trade Regulation / Thomas Cottier -- Trade, Commerce and Employment: The Evolution of the Form and Regulation of the Employment Relationship in Response to the New Information Technology / Kenneth G. Dau-Schmidt -- Crime, Security and Information Communication Technologies: The Changing Cybersecurity Threat Landscape and Implications for Regulation and Policing / David S. Wall -- Genetic Engineering and Biological Risks: Policy Formation and Regulatory Response / Filippa Lentzos -- Audience Constructions, Reputations, and Emerging Media Technologies / Nora A. Draper, Joseph Turow -- Technology Wags the Law / Victor B. Flatt -- Law, Responsibility and the Sciences of the Brain/Mind / Stephen J. Morse -- Water, Energy and Technology: The Legal Challenges of Interdependencies and Technological Limits / Robin Kundis Craig -- Climate Engineering, Law and Regulation / Jesse L. Reynolds -- Carbon Capture and Storage / Richard Macrory -- Nuisance Law, Regulation, and the Invention of Prototypical Pollution Abatement Technology / Ben Pontin -- Are Human Biomedical Interventions Legitimate Regulatory Policy Instruments? / Karen Yeung -- The Common Good / Donna Dickenson -- Human Rights and Information Technologies / Giovanni Sartor -- Human Dignity and the Ethics and Regulation of Technology / t
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on August 8, 2017).
Keywords: Technology and law